Emergent biotechnology applications in urology: a mini review - Chang Liu; Alejandro Rivera Ruiz; Yingchun Zhang; Philippe Zimmern; Zhengwei Li; Zhengwei Li (Frontiers in Bioengineering and Biotechnology)
Technological advances have significantly impacted the field of urology, providing innovative solutions for diagnosis, treatment, and management of various urological disorders and diseases. This article highlights four groundbreaking technologies: whole-cell biosensors, optogenetic interventions for neuromodulation, bioengineered urinary bladder, and 3D bioprinting. Each technology plays a crucial role in enhancing patient care and improving clinical outcomes in urology. Advances in these fields underscore a shift towards precision diagnostics, personalized treatments, and enhanced regenerative strategies, ultimately aiming to enhance patient outcomes and address unmet clinical needs in urological diseases.